UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MUSIK NUSANTARA MELALUI PENDEKATAN APRESIASI PADA SISWA KELAS VIII C SMP NEGERI 5 PEMALANG - Erli Setiani Irianawati (Jurnal Penelitian Pendidikan, 2014)
There are still many students of Pemalang Junior High School 5who consider art and culture subject as an unimportant lesson compare with other subjects being tested in the national exam and that it is a mere complementary subject. This can be observed through the fact that there are many students who scored below schools academic standard, which is 75, and teachers have not applied the approach and effective teaching approaches to improve students achievement. The purpose of this research are (1) to find out the improvement of students’ motivation in learning national music through appreciationapproach, and (2) to determine the improvement of student learning outcomes in learning national music through appreciation approach.The approach used in this research is classroom action research with four stages: (1) planning, (2) implementation, (3) observation, (4) analysis and reflection. Results were analyzed by quantitative descriptive techniques to describe the data and compare the findings with predetermined indicators. The research results shows that the process of learning national music through appreciation approach can improve students’ motivation and learning outcomes. These improvements are influenced by the activities of students in the learning process derived from the observations using the observation sheet, interviews, documentation, and performance of the students in singing, as well as the score of their daily tests. By the end of the second cycle, thestudents activity improvements increase from 50% to 70%.